Strengthening the Roles and Duties of the Audit Committee and the Auditors as stated in the Securities and Exchange Act B.E. 2535 - Kesaprakorn, Nares (Nitipat NIDA Law Journal, 2022)
This article aims to explore the roles and duties, good practices, communication, and coordination between auditors and Audit Committee and to examine factors promoting the accuracy and efficiency in their roles and duties in orders to increase the mechanism for the law enforcements of Securities Regulation more efficiently. Strengthening the roles and duties of the Audit Committee and the auditors as stated in the Securities and Exchange Act B.E. 2535, Section 89/25 and the relevant notifications of the Capital Market Supervisory Board, which is in accordance with the guidelines of the law Sarbanes-Oxley Act of the United States and Corporate Governance (CG) principles, is a very crucial issue for the management of listed companies on the Stock Exchange that raised funds by issuing securities for sale to the public or any person to be used as a source of money for business operations.Promoting the duties and roles of the Audit Committee and the auditors is a significant mechanism in increasing the law enforcement efficiency because auditor and Audit Committee are expected to perform their roles and duties with independence, free from interest, and have the competence to apply their knowledge and professionalism to assist the auditors and Auditor Committee in assessing the management of company. In case the auditor finds practices of a director, a manager, or person responsible for the operation of the juristic person that appear to be suspicious of committing management malpractice in a fraudulent manner, the auditor is obliged to inform the company’s auditor committee of the facts for further inspection without delay. And, the Auditor Committee shall report the results of the preliminary audit to the the Securities and Exchange Commission (SEC) Office and the auditor for acknowledgement within thirty days from the date of being notified by the auditor. If the Auditor Committee does not take action, the auditor shall notify the SEC Office of the practice that shall be reported. If an auditor or the Audit Committee of a company violates or fails to comply, he or she shall be liable to a fine not exceeding one hundred thousand baht. The study has found that the provision of the law stating the auditor obligations to report and proceed for obtaining facts about suspected malpractice is still unclear, and it should be addressed with clarity and concrete format, rather than written in principle. Additionally, to promote the performance efficiency of the auditor and the Audit Committee, priorities should be given to increasing “Independence” of auditor and the Audit Committee along with the importance of Audit Committee Charter, which shall be deemed the Audit Committee’s obligations and failure to perform it shall be considered a neglect of duties.